Soil type and soil preparation influence vine development and grape composition through its impact on vine water and nitrogen status - Leeuwen Cornelis, van; Rességuier Laure, de; Séverine, Mary; Coralie, Laveau; Etienne, Mousset-Libeau; Elisa, Marguerit; Jean-Philippe, Roby; Amélie, Quiquerez (E3S web of conferences, 2018)
The influence of soil type and preparation on vine development and grape composition was investigated in a 50 ha estate located in Saint-Emilion (Bordeaux, France) and planted predominantly with Merlot. Part of the vineyard was planted down the slopes and another part of the vineyard was planted on terraces, where soils were profoundly modified through soil preparation. Grape composition (berry weight, sugar, total acidity, malic acid and pH), vigor (pruning weight), vine nitrogen status (Yeast Available Nitrogen (YAN) in grapes) and vine water status (δ 13 C) was measured at a very high density grid of 10 data points per hectare. Water deficit was globally weak over the estate because of high soil water holding capacity whereas vine nitrogen status was highly variable. Vine vigor and grape composition were predominantly driven by vine nitrogen status. On terraces, where soils were deep, due to invasive soil preparation, water deficits were particularly small or non-existent and vine nitrogen status was highly variable. Grape quality potential was medium to low, except in places with low nitrogen status, but at the expense of low yields. On parcels planted down the slopes water deficits were recorded because vine rooting was limited by compact subsoils. Vine nitrogen status was homogeneous. Grape quality and yield were medium to high and relatively homogeneous. When possible, downhill plantations are to be preferred over terraces because in the latter vine yield and quality parameters are highly variable because of massive soil movements prior to plantation.